Structures of the E46K Mutant-Type α-Synuclein Protein and Impact of E46K Mutation on the Structures of the Wild-Type α-Synuclein Protein - Wise-Scira, Olivia (American Chemical Society, 2013)
[Image: see text] The E46K genetic missense mutation of the wild-type α-synuclein protein was recently identified in a family of Spanish origin with hereditary Parkinson’s disease. Detailed understanding of the structures of the monomeric E46K mutant-type α-synuclein protein as well as the impact of the E46K missense mutation on the conformations and free energy landscapes of the wild-type α-synuclein are required for gaining insights into the pathogenic mechanism of Parkinson’s disease. In this study, we use extensive parallel tempering molecular dynamics simulations along with thermodynamic calculations to assess the secondary and tertiary structural properties as well as the conformational preferences of the monomeric wild-type and E46K mutant-type α-synuclein proteins in an aqueous solution environment. We also present the residual secondary structure component conversion stabilities with dynamics using a theoretical strategy, which we most recently developed. To the best of our knowledge, this study presents the first detailed comparison of the structural and thermodynamic properties of the wild-type and E46K mutant-type α-synuclein proteins in an aqueous solution environment at the atomic level with dynamics. We find that the E46K mutation results not only in local but also in long-range changes in the structural properties of the wild-type α-synuclein protein. The mutation site shows a significant decrease in helical content as well as a large increase in β-sheet structure formation upon E46K mutation. In addition, the β-sheet content of the C-terminal region increases significantly in the E46K mutant-type αS in comparison to the wild-type αS. Our theoretical strategy developed to assess the thermodynamic preference of secondary structure transitions indicates that this shift in secondary structure is the result of a decrease in the thermodynamic preference of turn to helix conversions while the coil to β-sheet preference increases for these residues. Long-range intramolecular protein interactions of the C-terminal with the N-terminal and NAC regions increase upon E46K mutation, resulting in more compact structures for the E46K mutant-type rather than wild-type αS. However, the E46K mutant-type αS structures are less stable than the wild-type αS. Overall, our results show that the E46K mutant-type αS has a higher propensity to aggregate than the wild-type αS and that the N-terminal and C-terminal regions are reactive toward fibrillization and aggregation upon E46K mutation and we explain the associated reasons based on the structural properties herein. Small molecules or drugs that can block the specific residues forming abundant β-sheet structure, which we report here, might help to reduce the reactivity of these intrinsically disordered fibrillogenic proteins toward aggregation and their toxicity.